2022
DOI: 10.3390/su14063153
|View full text |Cite
|
Sign up to set email alerts
|

Can Informal Savings Groups Promote Food Security and Social, Economic and Health Transformations, Especially among Women in Urban Sub-Saharan Africa: A Narrative Systematic Review

Abstract: This narrative review aimed to identify if roles of common informal savings groups known as Accumulating Savings and Credit Associations (ASCAs) or Rotating Savings and Credit Associations (ROSCAs) can play a significant role in mitigating food insecurity, socioeconomic inequality, promoting health, and/or increasing agency in women in urban sub-Saharan Africa (SSA). These organizations exist in most low- and middle-income countries (LMICs) worldwide under various names. A comprehensive search of scholarly out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…Amponsah et al (2023) found that participation in CSGs significantly increased the agricultural productivity and income of the participants. Another important aspect of this topic is the role that CSGs play in food security, although Lukwa et al (2022) mention that this is not the main reason which drives the members to participated in these groups. Although this topic is included based on the algorithm, in fact it concerns the entire primary sector and there is evidence regarding fishing (Lieng et al, 2018) and livestock breeding (Okello et al, 2020).…”
Section: Sustainability and Performancementioning
confidence: 99%
“…Amponsah et al (2023) found that participation in CSGs significantly increased the agricultural productivity and income of the participants. Another important aspect of this topic is the role that CSGs play in food security, although Lukwa et al (2022) mention that this is not the main reason which drives the members to participated in these groups. Although this topic is included based on the algorithm, in fact it concerns the entire primary sector and there is evidence regarding fishing (Lieng et al, 2018) and livestock breeding (Okello et al, 2020).…”
Section: Sustainability and Performancementioning
confidence: 99%
“…According Lukwa et al, 2022) saving groups play critical roles in advancing socio-economic and health transformation especially among women in Sub-Saharan Africa. Also, saving groups play important roles in enhancing food security and improving the dietary intake besides access to healthy foodstuffs among households (Ogwal, Amot & Mwesigwa, 2020, Mwesigwa & Mubangizi, 2019, Mwesigwa, 2016.…”
Section: The Significance Of Saving Groups In Poverty Reductionmentioning
confidence: 99%
“…Therefore, during crises such as the covid-19 pandemic which hurt people's livelihoods, stokvels provided a lifeline through provision of loans for purchase of staple foods (PMBEJD, 2020). In view of the role stokvels in food system resilience, Lukwa et al (2022) highlight the need to develop partnerships and collaborations between stokvels and relevant food system stakeholders.…”
Section: Stokvels In South Africamentioning
confidence: 99%